2002
DOI: 10.1128/mcb.22.7.1961-1970.2002
|View full text |Cite
|
Sign up to set email alerts
|

The PHD Type Zinc Finger Is an Integral Part of the CBP Acetyltransferase Domain

Abstract: Histone acetyltransferases (HATs) such as CBP and p300 are regarded as key regulators of RNA polymerase II-mediated transcription, but the critical structural features of their HAT modules remain ill defined. The HAT domains of CBP and p300 are characterized by the presence of a highly conserved putative plant homeodomain (PHD) (C4HC3) type zinc finger, which is part of the functionally uncharacterized cysteinehistidine-rich region 2 (CH2). Here we show that this region conforms to the PHD type zinc finger con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 64 publications
4
70
0
3
Order By: Relevance
“…Thus, the RAG2 C terminus might directly facilitate changes in chromatin structure or, more likely, facilitate assembly of the RAG1͞2 complex on RSSs wrapped in chromatin. The association of other PHD-containing proteins with chromatin remodeling and modification (21)(22)(23)(24) is consistent with such a role for RAG2 in influencing the accessibility of antigenreceptor loci. In this context, the PHD motif of RAG2 might serve a unique, undefined function in promoting accessibility of V H and V␤ segments.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Thus, the RAG2 C terminus might directly facilitate changes in chromatin structure or, more likely, facilitate assembly of the RAG1͞2 complex on RSSs wrapped in chromatin. The association of other PHD-containing proteins with chromatin remodeling and modification (21)(22)(23)(24) is consistent with such a role for RAG2 in influencing the accessibility of antigenreceptor loci. In this context, the PHD motif of RAG2 might serve a unique, undefined function in promoting accessibility of V H and V␤ segments.…”
Section: Discussionsupporting
confidence: 51%
“…Consistent with this notion, studies of Abelson murine leukemia virus-transformed pre-B cells have suggested that the noncore regions of RAG1 are important for IgH locus D H -to-J H rearrangement (17), whereas the C terminus of RAG2 is more important for V H -to-DJ H rearrangement than for D H -to-J H rearrangement (18). The C terminus of RAG2 is predicted to fold into a plant homeodomain (PHD) (19,20), a motif found in a number of chromatin-associated proteins including some that have chromatin-modifying activities (21)(22)(23)(24).…”
Section: Uring B and T Cell Development The Ig And T Cell Receptormentioning
confidence: 99%
“…The balance between acetylation and deacetylation of specific factors is regulated at an additional level, since SIRT1 itself deacetylates several HATs and regulates their enzymatic activities (Kalkhoven et al, 2002;Thompson et al, 2004). SIRT1 directly interacts with PCAF and p300 to promote their deacetylation and enzymatic inactivation (Fulco et al, 2003;Motta et al, 2004;Cohen et al, 2004a).…”
Section: Sirt1 Promotes Replicative Senescence During Prolonged Exposmentioning
confidence: 99%
“…pRc/RSV-CBP-HA and pRP265-GST-p300-HAT were kindly provided by R. Giles (20) and R. Vries (21), respectively. Gal4-DBD-CBP-HA constructs were a kind gift of E. Kalkhoven (22). pRL-TK (Tk-Renilla luciferase) was purchased from Promega.…”
Section: Methodsmentioning
confidence: 99%